Optimization of Bio-Char Production from Palm Kernel Shells as Metallurgical Coke Using Response Surface Methodology - Hariyadi Asful; Purwanto Moch; Mubarok Fikan R; Vantoni Rama (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2026)
This research focuses on optimizing biochar production from palm kernel shells (PKS) as an environmentally friendly alternative to metallurgical coke. PKS was chosen due to its abundance, high lignocellulose content, and competitive heating value. The conversion process was carried out via pyrolysis at temperatures of 400–700°C with varying residence times. To ensure the biochar produced meets metallurgical coke specifications, this research uses a Response Surface Methodology (RSM) approach with a Central Composite Design (CCD) model to optimize temperature and time parameters. The initial stage involved pre-treatment using water leaching, successfully reducing ash content from 5.68% to 1.25%. Optimization results show that at a temperature of 600–700°C with a residence time of 2–3 hours, the resulting biochar exhibits characteristics that comply with metallurgical coke standards, such as high fixed carbon content (>85%), low ash content (<6%), and a calorific value of 7200 kcal/kg. Moreover, increasing pyrolysis temperature and time also reduces volatile matter and moisture content, resulting in more stable and efficient biochar. This research provides a real solution for utilizing PKS waste as an alternative raw material for the steel industry, reducing dependence on imported coal-based coke. The results of the RSM optimization indicate an optimal temperature of 612°C and a residence time of 3 hours.